Konflik Ekonomi Gerakan Penolakan Tambang di Konawe Kepualauan - Lamondo, Lamondo (Robust: Research of Business and Economics Studies, 2022)
This study aims to determine the mining process in the Konawe Islands and the motives for community rejection. The approach used in this study is qualitative with a case study method. Data was collected with interview and documentation techniques. This research shows that mining has several obstacles, including rules regarding environmental impact analysis and regional spatial plans. The motive for rejection is the community's partiality to a safe living environment for all living things. The results conclude that Through the authority of regional autonomy, many forms of legislation are made access to the entry of this mining industry under the pretext of development and economy. Mining alienates traditional communities from their land. Ecofeminism, as a feminist environmental ethics supported by Islamic religious teachings, is considered to be able to suppress anthropocentric ethics that tend to be masculine as well as capitalist.